Progress in the analysis of the electrical generator of the heart - Chaikovsky, Illya; Budnyk, Mykola; Najafian, Mokhammad; Martynenko, Serhiy; Dovbysh, Anatoly; Budnyk, Vitaly; Kovalenko, Oleksandr (Видавництво Львівської політехніки, 2010)
Aim of study is to develop understanding of the heart electric generator based on classification of current density distribution (CDD) maps with help of information-extreme intellectual technology (IEIT). Errorfree decision rules were obtained in learning population. Decision rule for test Healthy–CAD was examined based on 203 healthy volunteers and 256 CAD pts and sensitivity and specificity equal to 93% and 87 %, respectively, have been achieved.
Keywords: pattern recognition; information-extreme intellectual technology (IEIT); current density distribution